Melanonychia striata with lentiginous pigmentation: a rare case report - Shah, Dhyey Nimish; Patel, Aanal; Solanki, Dhimahi A.; Patel, Gopika A.; Patel, Krina B.; Lalchandani, Deeksha (International Journal of Research in Dermatology, 2025)
Melanonychia is characterized by brown to black discolouration of nail plate of the finger nail or toe nail due to pigment deposition. The aetiology of melanonychia ranges from benign causes that are nevus and lentigines to a malignant one like melanoma, which is however rare. Other aetiology includes post-traumatic, nutritional deficiency, infections, constitutional etc. We report here; a nine-year-old male child who presented to us with concern of pigmented nail bands. A dermoscopic and histopathological evaluation indicated the presence of an intradermal nevus along with concurrent lentiginous pigmentation, which is a rare occurrence.